Pre-design of laterally supported stair steps - Santos, José (2019)
It is becoming increasingly common to design monumental staircases and their steps with elevated stiffness and low mass, obtaining high natural frequencies, off the range of frequencies that are excitable by pedestrians. However, this sometimes leads to unacceptable levels of vibration, with impulsive responses. In many cases the dynamic behaviour of steps is almost independent from the rest of the staircase, causing a phenomenon de signated as local vibrations, which could be much more severe than the global vibrations of the staircase. In order to avoid this problem, this paper presents a simplified expression to pre-design stair steps which guarantee that excessive vibrations will not occur, without the need to perform a dynamic analysis. The ex pression was deduced based on the results of an experimental campaign, several numerical analyses and a theoretical analysis. During this study it was necessary to define an acceptable limit of vibrations specific for this type of vibration, which affects mainly the feet of pedestrians. The expression deduced is easy to apply because it depends only of vertical stiffness of the step. Finally, the pre-design expression is also applied to the staircase used in the experimental campaign, and it was concluded that it would be easy to avoid excessive vibrations, with a negligible cost increase.